2016
DOI: 10.15412/j.jpcp.06040203
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Self-Awareness Training with Painting on Self-Efficacy among Orphaned Adolescents

Abstract: Objective: Self-awareness is the ability to accurately perceive the aspects of our personality, behavior, emotions, and motivations. It is the foundation of all kinds of emotional restraints. Moreover, the feeling of having control over everything is associated with improved mental health. Self-awareness skills are characterized as a set of coping and self-management skills that increase self-efficacy. Methods:This semi-experimental randomized controlled study was conducted on 80 individuals divided into an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Esmaeilinasab et al, 2011;Hajia et al, 2011;Nabors et al, 2000;Srikala & Kumar, 2010) also with deficit, diseases, or social disadvantages (e.g. Hatami et al, 2016;Kazemi et al, 2014;Shakeri et al, 2015;Sobhi-Gharamaleki & Rajabi, 2010). For example, Kazemi et al (2014) found that the experimental group of primary school children with dyscalculia had a significant increase in the self-esteem and communication skills than the control group.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esmaeilinasab et al, 2011;Hajia et al, 2011;Nabors et al, 2000;Srikala & Kumar, 2010) also with deficit, diseases, or social disadvantages (e.g. Hatami et al, 2016;Kazemi et al, 2014;Shakeri et al, 2015;Sobhi-Gharamaleki & Rajabi, 2010). For example, Kazemi et al (2014) found that the experimental group of primary school children with dyscalculia had a significant increase in the self-esteem and communication skills than the control group.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…Moreover, Hajia et al (2011) verified that the life skills training increased happiness, emotion regulation, psychological health, and social relationships in the experimental group of university students, compared to the control group. More recently, Hatami et al (2016) found that orphaned adolescents scored higher in self-efficacy and selfawareness skills after the intervention focused on life skills training than a control group. Only few evidences demonstrated that these life skills trainings not always are useful (or partially useful) to increase the social and life skills (e.g.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…Selfawareness is the potential in individuals that must be developed. Hatami, et al (2016) explain self-awareness is the ability to accurately understand aspects of our personality, behavior, emotions, and motivation. This is the foundation of all kinds of emotional restraints.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies make self-awareness a factor that influences other behaviors, such as discipline, free sex, life satisfaction, work support, and so on (Hansen, 2009;Sharifnasab & Sadrezade, 2011;Thiel 2011;Weinberg 2011;G. Strawson 2011;Akbari and Akbari, 2013;Snowdon 2014;Stonehouse, 2015;Maharani and Mustika, 2016;Dariyo, 2016;Ugur & Stevens, 2015;Hatami et al, 2016;Kalayarasan & Solomon, 2016;Evarist, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There was a statistically significant difference in the studied nurses' mean self-efficacy and sociotropy autonomy scores before and after receiving the education for increasing their self-awareness. Numerous studies also have supported that self-awareness training increased self-efficacy (Hatami et al 2016;Sevari & Manshedavi 2015;Umaru & Umma 2015;Ahmed & Elmasri 2011;Engin & Cam 2009).…”
Section: Control Interventionmentioning
confidence: 96%